The Effect of Face to Face Education on Controling Asthma at Dr. Sosodoro Djatikoesoemo Bojonegoro Hospital - Arum Rahmawati Virgin; Muhammad Amin; Makhfudli Makhfudli (International Journal of Nursing and Health Services (IJNHS), 2020)
Control of asthma is an important factor in the long-term treatment of asthma. Knowledge of controlled behavior is an action to be performed for the treatment of asthma patients. This study aims to determine the effect of face to face education intervention based on the Theory of Planned Behavior against the asthma control behavior. A quasi-experimental study design, pre and post test with an equivalent control group. Seventy-four samples were recruited using purposive sampling technique. The research was conducted by providing a TPB-based face to face education intervention for 1 month. Data analysis was performed and presented in descriptive statistics, and significant findings were computed using wilcoxon signed rank test. The results showed that face to face education was positive effect on controlling asthma (p=0,000). A Theory Of Planned Behavior-based education intervention has an effect in enhancing asthma control behavior